The Views and Positions of Imam Al-Qurtubi on Usury (Riba) Through His Book Al-Jami’ li-Ahkam al-Quran – A Presentation and Analysis - Aamer , Basem (Jordan Journal of Islamic Studies, 2025)
This research examines the views of Imam Al-Qurtubi on the issue of usury (riba) as presented in his book Al-Jami’ li-Ahkam al-Quran. It focuses on the Quranic verses related to riba, reflecting on Al-Qurtubi’s interpretations and positions on these issues and rulings. The study systematically analyzes Al-Qurtubi’s comments on riba in his Tafsir, particularly in the chapters of Al-Baqarah, Al-Imran, An-Nisa, and Ar-Rum. The issues are categorized into topics such as the concept and reality of riba, its types and classifications, its application in trade, its rationale in transactions and money, the rulings on riba-related contracts, and the consequences of riba in this life and the hereafter. The study begins with a brief introduction to Imam Al-Qurtubi, his key works, and the significance of Al-Jami’ li-Ahkam al-Quran, as well as the methodology he used in this book. The research concludes with key findings and recommendations. The research concludes with several important results, notably that Imam Al-Qurtubi adhered to the methodology of early Islamic jurists in his interpretation of riba and did not deviate from their views on any of the issues discussed. It also highlights his fairness, pursuit of truth, and avoidance of sectarian bias.